Glycated albumin in pregnancy: reference intervals establishment and its predictive value in adverse pregnancy outcomes - Dong, Ying (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Many efforts have been focused on the alternative glycemic marker glycated albumin (GlyA) and its application in pregnancy during which profound physiological changes take place. Our objective was to determine the reference intervals (RIs) of GlyA in healthy Chinese pregnant women and to assess the predictive value of serum GlyA in adverse pregnancy outcomes. METHODS: Totally 421 healthy subjects including 137 in the first trimester, 152 in the second trimester, and 132 in the third trimester were enrolled from March to July 2019, for the purpose of establishing the trimester-specific RIs of GlyA. In addition, 67 pregnant women diagnosed with GDM were enrolled at 24–28 weeks of gestation. The diagnostic value of GlyA for GDM patients was evaluated and compared with that of fasting plasma glucose (FPG) at 24–28 weeks of gestation. The association between GlyA in the late pregnancy and the adverse pregnancy outcomes was analyzed with the data collected from January to June 2018 at our hospital. RESULTS: The estimated RIs of GlyA in present study were 11.26–15.10%, 10.04–13.50%, and 9.76–13.09% in the first, second, and third trimesters respectively. The areas under receiver operating characteristic (ROC) curves were 0.503 for GlyA and 0.705 for FPG. More importantly, the GlyA level in the third trimester was not more elevated in the patients with adverse pregnancy outcomes including large for gestational age (LGA), preterm delivery, hypertension and preeclampsia (PE). The exception was made with the GDM patients who suffered from postpartum hemorrhage and had significantly higher GlyA levels than the control group. CONCLUSIONS: Our results showed that the GlyA was continuously decreased as the gestational age went up. The GlyA testing has limited value in diagnosing GDM and predicting adverse pregnancy outcomes.